2019
DOI: 10.1080/10717544.2019.1654040
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of plantamajoside and sorafenib by a multi-functional nanoparticle to combat the drug resistance of hepatocellular carcinoma through reprograming the tumor hypoxic microenvironment

Abstract: Sorafenib (SOR) is a multi-kinase inhibitor that was approved as the first-line systematic treatment agent of hepatocellular carcinoma (HCC). However, the anti-cancerous effect of SOR is dramatically impaired by the drug resistance, insufficient accumulation at tumor tissues, and limited tumor inner penetration. To combat the above issues, the PLA-based nanoparticles were first fabricated and co-loaded with SOR and plantamajoside (PMS), natural herbal medicines that possess excellent anti-cancerous effect on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…have been explored in depth in the tumour microenvironment, as NP penetration and stability are challenging in solid tumours 107,146 . Many characteristics of the tumour microenvironment -including the vasculature, interstitial fluid pressure and extracellular matrix (ECM) density -contribute to the limited permeation and penetration of NPs 3,[147][148][149][150] . Thus, the exact cause of successful NP accumulation in tumours has been highly debated, with only a few established trends correlating NP design to tumour delivery.…”
Section: Local Np Distribution Barriers To Local Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…have been explored in depth in the tumour microenvironment, as NP penetration and stability are challenging in solid tumours 107,146 . Many characteristics of the tumour microenvironment -including the vasculature, interstitial fluid pressure and extracellular matrix (ECM) density -contribute to the limited permeation and penetration of NPs 3,[147][148][149][150] . Thus, the exact cause of successful NP accumulation in tumours has been highly debated, with only a few established trends correlating NP design to tumour delivery.…”
Section: Local Np Distribution Barriers To Local Distributionmentioning
confidence: 99%
“…The heterogeneity of tumour microenvironments generates many obstacles to successful NP delivery, including reduced permeation. Within the tumour environment, cells may overproduce or generate altered ECM components that result in a dense ECM that physically hinders NP delivery 147 149 . This is especially true for cationic NPs as they adhere to the negatively charged tumour ECM, reducing permeation 71 , 153 .…”
Section: Biological Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…NPs were produced and co-loaded with Sorafenib and plantamajoside and decorated with a polypeptide which specifically binds to biomolecules overexpressed on the surface of cancer cells. The authors demonstrated that this functionalization improved drug accumulation and penetration at tumor sites, resulting in a strong inhibition of tumor growth [ 168 ]. Li et al [ 169 ] formulated a dual-targeting delivery system for enhanced HCC therapy by encapsulating Sorafenib and anti-miRNA21 (an antisense oligonucleotide with great potential in cancer therapy) in pentapeptide-modified reconstituted high-density lipoprotein NPs.…”
Section: Nanoparticles Of Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…For the treatment of hepatocellular carcinoma, Zan and colleagues described the results obtained using a multifunctional delivery system in which polymeric NCs were co-loaded with two natural anti-cancer molecules that are able to reduce the tumor hypoxic microenvironment decorated with a cancer-related biomarker that also increases cellular uptake. The resulting multi-functional NC significantly reduced hypoxia and tumor drug resistance, thereby increasing the therapeutic effects [293]. Although NCs directed at cancer tissues limit the possible toxicity of the therapy, optimization of the dose and administration reduces the risk of their non-specific accumulation in normal organs.…”
Section: Simulated Metronomic Therapies: Nanocarriers For Cancer Therapymentioning
confidence: 99%